Effect of Air-Fuel Ratio to Temperature Distribution of Pulverized Coal Boiler - Ronaldo Eng; Abrar Riza; Harto Tunajaya (Indonesian, 2021)
A three-dimensional numerical simulation was carried out to study the pulverized coal combustion process in a tangentially fired pulverized pulverized-coal boiler. The realizable k-epsilon model for gas coupled with discrete phase model for pdf-mixtures, P-1 radiation model for radiation. The characteristics of the flow field, particle motion, temperature distribution, and species components were numerically investigated. It is found that an ideal turbulent flow and particle trajectory can be observed in this unconventional pulverized-coal furnace. With the application of air-fuel ratio, combustion takes place near the burner sets. Within the limits of air-fuel ratio, more steady combustion process is achieved. The numerical simulation results reveal that at the air-fuel ratio of 5,7645;11,529; and 23,058 the simulation achieved the maximum temperature of 1916,64? with 91,664% increase for the air-fuel ratio of 11,529, 1519,97? with 51,997% increase for the air-fuel ratio of 23,058, and 1587,15? with 58,715% increase with the air-fuel ratio of 5,7645. The numerical results reveal that air-fuel ratio affects the combustion process in the pulverized-coal boiler simulation.